Rather a trigger than a cause of change: Responses of firms and workers to the statutory minimum wage in Germany - Andreas Koch; Andrea Kirchmann; Marcel Reiner; Tobias Scheu; Holger Bonin (Institut für Angewandte Wirtschaftsforschung (IAW), 2018)
The introduction of the statutory minimum wage in Germany directly affected firms with wage earners paid less than EUR 8.50 per hour. This paper studies a variety of responses by employers and employees to adapt to this shock, in particular changes in compensation packages, employment at the extensive and intensive margin, working conditions, and position in product markets. Strategies of non-compliance are also in focus. The analysis is qualitative and based on 131 semi-structured, in-depth interviews with firm representatives, workers and members of work councils. A key finding is that while many firms and workers changed behavior with the introduction of the minimum wage, these changes are less response to concomitant changes in labor costs. Rather, it appears that the reform at many workplaces served as a catalyst to trigger or accelerate pending change processes.
Keywords: J08; J28; J81; 330; Minimum wage; Interview-based approach; Germany